Assessment of River-Aquifer Interaction and Nitrogen Contamination in an Agricultural Zone Located in the Guarani Aquifer System Outcrop Area - CAMILA DE LIMA; LUDMILA V. BATISTA; LIA N. GARPELLI; VINÍCIUS DOS SANTOS; CAROLINA S. QUAGGIO; DIDIER GASTMANS (Anais da Academia Brasileira de Ciências, 2023)
Abstract The excessive use of nitrogen fertilizers is responsible for an increase in nitrate concentrations in water bodies, which in the future could led to an irreversible contamination compromising the water resource quality. In this way, understand the water movement within a watershed and evaluate the impacts related to agricultural practices is relevant for water management, especially in an environmental fragile region, such as the outcrop area of the Guarani Aquifer. Water samples from a small watershed located at the Guarani Aquifer region in São Paulo state, representing surface water and groundwater discharge in riverbeds from two creeks, as well as groundwater (springs and wells) were collected for isotopic ratios (δ18O e δ2H) and nitrate determination. The results indicated that the river flow is mostly supplied by groundwater discharge, and despite the observed concentrations of nitrate in groundwater reaching the creeks, the current scenario indicate contamination in the surface water, above the regulatory levels. Therefore, the expansion in sugarcane production increases the possibility that the released nitrate reaches high levels in the future in this watershed.